Characteristics of methane combustion using H2 injection in a turbulent fluidized bed of inert particles. (29th June 2021) - Jo, Sungkwon; Cho, Donghyun; Kim, Kwan-Tae
Highlights: Methane combustion in fluidized beds with inert particles was investigated. Methane conversion with H2 injection in fluidized beds is 4 times that without H2. Temperature for complete methane combustion is reduced by injecting H2. Abstract: The characteristics of methane combustion were investigated in a fluidized bed reactor containing inert SiO2 particles in the temperature range 700–800 °C. In particular, the methane was combusted using H2 injection as an ignition source to initiate combustion at the relatively low temperature of 700 °C. It was found that complete combustion can be achieved at a bed temperature above 870 °C without ignition and at 800 °C with ignition. Even though the fast gaseous combustion of methane was initiated by ignition, the fast chain reaction was quenched under the condition of a bed temperature of less than 800 °C and insufficient residence time compared with the ignition delay at a given bed temperature. Moreover, it was confirmed that whereas NO x emission is reduced by decreasing the combustion temperature, the CO concentration of the exhaust gases increases drastically.